Aniline‐Promoted Cyclization–Replacement Cascade Reactions of 2‐Hydroxycinnamaldehydes with Various Carbonic Nucleophiles through In Situ Formed N, O‐Acetals. Issue 27 (27th May 2016) - Yu, Chenguang; Huang, He; Li, Xiangmin; Zhang, Yueteng; Li, Hao; Wang, Wei
Abstract: In this study, we report the harnessing of new reactivity of N, O ‐acetals in an aminocatalytic fashion for organic synthesis. Unlike widely used strategies requiring the use of acids and/or elevated temperatures, direct replacement of the amine component of the N, O ‐acetals by carbon‐centered nucleophiles for C−C bond formation is realized under mild reaction conditions. Furthermore, without necessary preformation of the N, O ‐acetals, an amine‐catalyzed in situ formation of N, O ‐acetals is developed. Coupling both reactions into a one‐pot operation enables the achievement of a catalytic process. We demonstrate the employment of simple anilines as promoters for the cyclization–substitution cascade reactions of trans ‐2‐hydroxycinnamaldehydes with various carbonic nucleophiles including indoles, pyrroles, naphthols, phenols, and silyl enol ethers. The process offers an alternative approach to structurally diverse, "privileged" 2‐substituted 2 H ‐chromenes. The synthetic power of the new process is furthermore shown by its application in a 2‐step synthesis of the natural product candenatenin E and for the facile installation of 2‐substituted 2 H ‐chromene moieties into biologically active indoles. Abstract : Cascade catalysis : New reactivity of N, O ‐acetals has been harnessed in an aminocatalytic cascade fashion for the efficient synthesis of 2‐substituted 2 H ‐chromenes.